2012
DOI: 10.1016/j.jjcc.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and its relation to insulin resistance in non-diabetic patients with slow coronary flow

Abstract: Patients with slow coronary flow have increased mean platelet volume which was associated with insulin resistance in non-diabetic slow coronary flow patients. TIMI frame counts correlated with mean platelet volume and increased insulin resistance. Thus, insulin resistance and platelet activity may have a role in the pathogenesis of slow coronary flow. Also, they may have a possible benefit as follow-up markers in non-diabetic patients with slow coronary flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
2
15
2
Order By: Relevance
“…Chou et al reported that serum UA levels were more strongly associated with insulin resistance in females than in males [29]. Insulin resistance contributes to increased platelet activation and MPV [30]. Thus, one possible explanation for the observed gender differences in the present study is that insulin resistance may play a role in the etiology of the relationship between UA and MPV.…”
Section: Discussionmentioning
confidence: 50%
“…Chou et al reported that serum UA levels were more strongly associated with insulin resistance in females than in males [29]. Insulin resistance contributes to increased platelet activation and MPV [30]. Thus, one possible explanation for the observed gender differences in the present study is that insulin resistance may play a role in the etiology of the relationship between UA and MPV.…”
Section: Discussionmentioning
confidence: 50%
“…Rapid resolution of insulin resistance occurs after delivery, suggesting a major contribution from placental hormones. The relationship between MPV and insulin resistance was demonstrated in some studies [20,21]. In vitro and in vivo studies showed that insulin inhibits platelet aggregation and activation in insulin-sensitive subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Arterial thrombosis and the proliferation of thrombi require that a sequence of coagulation reactions as well as platelet deposition occur on the thrombus surface. Adding pharmacologic concentrations of rFVIIa to hemophilic blood markedly increases platelet activation in the absence of tissue factor and decreases the tissue factor-independent APTT and tissue factor-relative prothrombin time [16],[18],[19]. Therefore, the administration of a combination of additional platelets and rFVIIa could significantly improve coagulation reactions, better than a single administration of either platelets or rFVIIa alone.…”
Section: Discussionmentioning
confidence: 99%